Microcystin-LR induced developmental toxicity and apoptosis in zebrafish (Danio rerio) larvae by activation of ER stress response. (August 2016) - Qi, Mei; Dang, Yao; Xu, Qinglong; Yu, Liqin; Liu, Chunsheng; Yuan, Yongchao; Wang, Jianghua
Abstract: Recent studies have demonstrated that cyanobacteria-derived Microcystin-LR (MC-LR) can cause developmental toxicity and trigger apoptosis in zebrafish ( Danio rerio ) larvae, but the underlying mechanisms remain largely unknown. In this study, we tested the hypothesis that the mechanism by which MC-LR induces developmental toxicity is through activation of endoplasmic reticulum (ER) stress. MC-LR (4.0 μM) exposure through submersion caused serious developmental toxicity, such as malformation, growth delay and decreased heart rates in zebrafish larvae, which could be inhibited by ER stress blocker, tauroursodeoxycholic acid (TUDCA, 20 μM). Meanwhile, acridine orange (AO) staining showed TUDCA could rescue cell apoptosis in heart area in zebrafish larvae resulted by MC-LR exposure. Real-time polymerase chain reaction (real-time PCR) analysis demonstrated that MC-LR induced activation of ER stress which consequently triggered apoptosis in zebrafish larvae. Protein expression examined by western blot indicated that MC-LR could activate MAPK8/Bcl-2/Bax pathway and caspase-dependent apoptotic pathway in zebrafish larva and the effects were mitigated by inhibition of ER stress. Taken together, the results observed in this study suggested that ER stress plays a critical role in developmental toxicity and apoptosis in zebrafish embryos exposed to MC-LR. Highlights: MCLR induced activation of ER stress which consequently triggered apoptosis in zebrafish larvae. MCLR could activate MAPK8/Bcl-2/Bax pathway and caspase-dependent apoptotic pathway in zebrafish larvae. Effects of MCLR on zebrafish larvae could be prevented by treatment with inhibitor of ER stress, TUDCA.